A STUDY OF POSTMODERN LITERATURE IN TRANSLATION AS ILLUSTRATED THROUGH THE SELECTED WORKS OF THOMAS PYNCHON - Barciński, Łukasz (My University, 2015)
The subject of the thesis is the analysis of the specificity of postmodern literature as illustrated through the Polish translation of novels by Thomas Pynchon. In order to find the most precise research tool for the analysis of such a complicated research subject, the thesis applies interdisciplinary approach combining the achievements of various disciplines such as: translation studies – foreignisation/domestication (Venuti), literary studies – polyphonicity (Bachtin), intertextuality (Kristeva), plasir/jouissance (Barthes), defamiliarisation/ostranenie (Shklovsky), philosophy – dissemination (Derrida), rhizomaticity (Deleuze, Guattari), psychoanalysis (Lacan), linguistics and information theory (Shannon). The practical analysis examines to what extent entanglements of textual signification (called rhizomes, a term introduced by Deleuze and Guattari) have been recreated in the Polish rendition by analysing the extent of the recreation of defamiliarisation. Foreignisation was recognized to be the adequate translation strategy to recreate the extent of defamiliarisation (which is relatively high in postmodern texts). The term entropy, derived from information theory, was applied to determine the extent of the recreation of defamiliarisation in the translation product i.e. the translated works by Thomas Pynchon.

Przedmiotem pracy jest analiza specyfiki przekładu literatury postmodernistycznej na przykładzie tłumaczenia powieści Thomasa Pynchona na język polski. W celu znalezienia jak najbardziej precyzyjnego aparatu badawczego dla analizy tak złożonego przedmiotu badań, praca stosuje podejście interdyscyplinarne łącząc osiągnięcia różnych dyscyplin takich jak: przekładoznawstwo - forenizacja/domestykacja (Venuti), literaturoznawstwo – polifoniczność (Bachtin), intertekstualność (Kristeva), plasir/jouissance (Barthes), defamiliaryzacja/ostranienie/uniezwyklenie (Szkłowski), filozofia – dyseminacja (Derrida), rizomatyka (Deleuze, Guattari), psychoanaliza (Lacan), lingwistyka oraz teoria informacji – entropia (Shannon). Praktyczna analiza skupia się na zbadaniu stopnia odtworzenia pewnych splotów sygnifikacji tekstu oryginału w tekście tłumaczenia, nazwanych na potrzeby pracy rizomami (od terminu wprowadzonego przez Deleuze’a i Guattariego) za pomocą zbadania stopnia defamiliaryzacji w porównywanych tekstach. Za strategię tłumaczeniowa adekwatną do odtworzenia stopnia defamiliaryzacji (który w tekstach postmodernistycznych utrzymuje się na wysokim poziomie) została uznana forenizacja. Zaczerpnięte z teorii informacji pojęcie entropii zostało wykorzystane w celu określenia stopnia odtworzenia defamiliaryzacji w produkcie przekładu tj. w przetłumaczonych utworach Thomasa Pynchona.
STUDIUM PRZEKŁADU LITERATURY POSTMODERNISTYCZNEJ NA PRZYKŁADZIE WYBRANYCH UTWORÓW THOMASA PYNCHONA
Keywords: postmodernism; foreignisation; rhizomaticity; literary translation; postmodernizm; forenizacja; rizomatyka; przekład literacki